Yahoo奇摩 網頁搜尋

  1. ...中得出y=3b/5, 即E=((3a-2m)/5, 3b/5) 設CE/ AE =r:1, 根據公式 E=( (-mr+a)/r+1 , b/r+1 ) = ((3a-2m)/5, 3b/5...

    分類:科學及數學 > 數學 2007年09月02日

  2. .../o61/billy_hywung/April07/Wave5.jpg Therefore, this expression can be regarded as a travelling wave. Afterwards, from (b...

  3. ...e) =ac^2x^3 + adx^2 +aex +bc^2x^2 + bdx +be =(ac^2)x^3 + (ad +bc^2)x^2 + ( ae +bd)x +be as coefficient of x*x*x is (ac^2) = 4 and coefficient of x ...

    分類:科學及數學 > 數學 2010年09月04日

  4. ...y)dy = 8 ∫dt lny = 8t+c where c is a constant y= Ae ^(8t) where A is a constant -----------(1) ...when t=0, y=20 20=A(1) y=20e^(8t) ---------(2) so expression for the number of cells after t hours...

    分類:科學及數學 > 數學 2008年01月29日

  5. (1) 圖片參考:http://i117.photobucket.com/albums/o61/billy_hywung/Oct07/Crazyhyp1.jpg

    分類:科學及數學 > 數學 2007年10月17日

  6. ...there4;BC:DE=AB:AD x:12=12:(12+4) x=9 ∴ AE :AC=AD:AB (y+6):y=4:3 1+6/y=4/3 6/y=1/3 y=18 &there4...

    分類:科學及數學 > 數學 2008年07月16日

  7. ... the question in Q.3 y(3) = 7 i.e. y = 7 when x = 3 From the expression , put y = 7, x = 3, we get: 4 = Ae ^[2/(-4)] A = 4e^2 So, the particular solution is: x - y = 4e^{2(x...

    分類:科學及數學 > 數學 2008年09月28日

  8. ...%E9%A6%AC%E5%B0%8F%E5% AE %9A%E7%90%86 2009-12-31 16:51:11 補充: 證明 若n不能整除a - b...

    分類:科學及數學 > 數學 2010年01月15日

  9. ...dx + e) = acx³ + adx² + aex + bcx² + bdx + be = acx³ + (ad+bc)x² + ( ae +bd)x + be If the coefficients of x³ and terms after...

    分類:科學及數學 > 數學 2012年08月21日

  10. ...not equal to-5 or 2,angle AEB = 90 degree, so 2 expressions are actually the same. If x = -5 or 2, point...039;s angle in semi-circle in Ch.10????so slope of AE times slope of BE =-1, since they are...

    分類:科學及數學 > 數學 2015年03月08日